Exploiting wastes in concrete proceedings of the international seminar held at the University of Dundee, Scotland, UK on 7 September 1999 - Dhir, Ravindra K.; Jappy, Trevor G. (Thomas Telford, 1999)
Topics covered in 'Exploiting Wastes in Concrete' include maximising the use of waste materials in concrete production and the use of alternative materials in concrete.
Keywords: Concrete -- Congresses.; Waste products as building materials -- Congresses.; Waste products -- Recycling -- Congresses.; elektronické knihy; electronic books